Effect of leukoreduction on inflammation in critically ill dogs receiving red blood cell transfusions: A randomized blinded controlled clinical trial. (6th July 2022) - Claus, Melissa A.; Poh, Denise; Smart, Lisa; Purcell, Sarah L.; Boyd, Corrin J.; Sharp, Claire R.
Abstract: Background: Prestorage leukoreduction of red blood cell (RBC) bags prevents accumulation of pro‐inflammatory mediators and experimentally attenuates post‐transfusion inflammation in healthy dogs. However, the effect of leukoreduction on post‐transfusion inflammation in critically ill dogs is unclear. Hypothesis: Dogs transfused with leukoreduced (LR) RBC will have lower concentrations of leukocytes, interleukin (IL)‐6, IL‐8, monocyte chemoattractant protein‐1 (MCP‐1), and C‐reactive protein (CRP) within 24 hours of post‐transfusion compared to dogs transfused with nonleukoreduced (NLR) RBC. Animals: Sixty‐one RBC‐transfused dogs (LR = 34, NLR = 27). Methods: Randomized, blinded, controlled preliminary clinical trial. Blood bag processing was randomized to create identically appearing LR and NLR bags. Group allocation occurred with transfusion of the oldest compatible RBC bag. Blood samples were collected pretransfusion and at 8 and 24 hours post‐transfusion for leukocyte count, IL‐6, IL‐8, MCP‐1, and CRP. Data were analyzed on an intention‐to‐treat basis using linear mixed effects models. Significance was set at P < .05. Results: No significant differences were found between groups in concentrations of leukocytes ( P = .93), IL‐6 ( P = .99), IL‐8 ( P = .75), MCP‐1 ( P = .69), or CRP ( P = .18) over time. Eleven LR dogs (32%) and 4 NLR dogs (15%) were euthanized in the hospital ( P = .14). No natural deaths occurred. Conclusions and Clinical Importance: No differences in inflammation biomarker concentrations were detected over time between dogs transfused with LR or NLR RBC, but heterogeneity likely hampered the ability to detect a difference with this sample size. The novel randomization and enrollment protocol was successfully implemented across 2 participating institutions and will be easily scaled up for a future multicenter clinical trial.